PENGGUNAAN BERBAGAI MEDIA TUMBUH UNTUK BIBIT MAHONI (Swietenia macrophylla) - Merisa Merisa; Afif Bintoro; Melya Riniarti (Jurnal Hutan Tropis, 2019)
Mahogany plants (Swietenia macrophylla) are the type of production forest plant that is able to overcome the scarcity problem of raw materials in the wood management industry, but there are some obstacles in their cultivation process. One of those inhibiting factor is the limited availability of top soil for nurseries media. Potential organic matter that could be mixed with top soil were husk charcoal compost, and sawdust. The purpose of this study was to obtained the best growth media for mahogany seedlings. This research was conducted at December 2017 – March 2018 in the green house of Agriculture Faculty Lampung University.This study used experimental method with Randomized Complete Block Design. The parameters measure were seed height, seed diameter, and number of leaves observed once every month for three months,leaf area, root length, root dry weight, shoot dry weight, total dry weight observed after at the end of the experiment. The obtained data were analyzed by Analysis of Variance (ANOVA) and continued with Least Significant Different (SLD). The results showed that the growth media consisted husk charcoal compost and top soil with composisition of 50% and 25% were performed better at increasing the mahogany growth than other treatments.